The duel [videorecording (DVD)] - Cook, Matt (Screenwriter); Harrelson, Woody; Hemsworth, Liam, 1990-; Braga, Alice; Cohen, Emory, 1990-; Price, Felicity; Zúñiga, José; Sadler, William, 1950- (Lionsgate, 2016)
A Texas Ranger investigates a series of murders in a small town and uncovers a dark secret about the town's charismatic leader.